Pengaruh Pendidikan Kesehatan Terhadap Perubahan Pengetahuan Dan Sikap Dalam Deteksi Dini Kekambuhan Gangguan Jiwa Wilayah Kerja Puskesmas Gatak Sukoharjo - Fatah, Ari, Arif Widodo, AKep.,M.Kes (2016)
ABSTRACT Mental disoreders have become a very serious epidemic to threaten global public health. Globally recurrence rates of mental patients reached 50% to 92%. Riskesdas year recurrence rates of mental disorders in 2013 of 1,7% of 1000 population. Sukoharjo district health office in 2013 2778cases patients with mental disorders ranked higest in Sukoharjo district. Previously public health never provide health education to patients with mental disorders. This research aims to influence Health Education Knowledge and Attitudes Toward Change In Early Detection Of Recurrence Of Mental Disorders Public Health Gatak Sukoharjo. This type of research used in this research is quasi experiment with preest-posttest one group design. The population in this study is the who family treat patient with mental disorders who live in Gatak village with a population of 98families. Sampling technique used is purposive sampling, in order to obtain 30 who family treat patient with mental disorders in Sukoharjo district Public Health Gatak as samples. Sampling in this research is purposive sampling, sample size in this study is 30 people. Analysis technique in this study using univariate and bivariate analysis using Wilcoxon signed ranks test previously conducted test data normality with Shapiro wilk. The results showed that knowledge mean pretest increased by 63,33 into 72,67. And the results showed that the pretest attitudes increased with result mean 60,20 be 67,67. Based on survey results revealed that the obtained probability value (p-value) of 0,000 at the knowledge that concluded there is an average difference is significant between pretest and posttest knowledge. As well as the values obtained probability (p-value) of 0,000 at the attitude that concluded there is an average difference between the attitudes of significant pretest and posttest attitude. Keywords : knowledge, attitude, health education, early detection, recurrence